2013
DOI: 10.1186/alzrt173
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of SPI-1865, a novel gamma-secretase modulator, in multiple rodent models

Abstract: IntroductionModulation of the gamma-secretase enzyme, which reduces the production of the amyloidogenic Aβ42 peptide while sparing the production of other Aβ species, is a promising therapeutic approach for the treatment of Alzheimer's disease. Satori has identified a unique class of small molecule gamma-secretase modulators (GSMs) capable of decreasing Aβ42 levels in cellular and rodent model systems. The compound class exhibits potency in the nM range in vitro and is selective for lowering Aβ42 and Aβ38 whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…This has led to the identification of a number of acidic GMSs with dramatic increases in potency and brain penetrance, and non-acidic GSMs based around a common scaffold that are also much more potent than the first generation NSAID-based GSMs (Figure 3) [155-172]. More recently triterpenoid natural product derived GSMs have been identified [173-174]. Overall there are subtle differences between these GSMs that may be therapeutically important.…”
Section: Gsmsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to the identification of a number of acidic GMSs with dramatic increases in potency and brain penetrance, and non-acidic GSMs based around a common scaffold that are also much more potent than the first generation NSAID-based GSMs (Figure 3) [155-172]. More recently triterpenoid natural product derived GSMs have been identified [173-174]. Overall there are subtle differences between these GSMs that may be therapeutically important.…”
Section: Gsmsmentioning
confidence: 99%
“…While the more potent acidic GSMs show the classic GSM signature of lowering Aβ1-42 and increasing Aβ1-38 [175], nonacidic GSMs increase Aβ1-37 and 1-38 and lower both Aβ1-40 and 1-42 [171]. In contrast, the triterpenoid GSM appears to be even more distinct lowering both Aβ1-38 and 1-42 [173-174]. These differential properties and comparison to GSIs are described in Table 2.…”
Section: Gsmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo profiling of (74) revealed that the acetate group was rapidly hydrolysed, in addition to the much slower hydrolysis of the tri-hydroxy THP. Further optimisation resulted in the identification of SPI-1865 (79) [74] ( Figure 3.17) (full structure not disclosed) which was selected as a development compound. In a mouse PK study, compound (75) displayed a moderate clearance of 3.1 L/h/kg, a high distribution volume of 12.1 L/kg, a long half-life of 6.5 h and moderate oral bioavailability at 37%, in addition to good CNS penetration with a Br:Pl ratio of 1.7 at the 6 h time point.…”
Section: Natural Productsmentioning
confidence: 99%
“…Based on these results combined with the efficacy and CYP inhibition data, compound 14 was chosen as a candidate for preclinical development. 10 We found that our initial lead compounds were likely DDI perpetrators due to their potent CYP3A4 inhibition. Structure-activity relationships aided by in silico modeling of these compounds revealed options for avoiding these liabilities.…”
mentioning
confidence: 99%